PENGARUH MODERNITAS SISWA DAN HASIL BELAJAR EKONOMI TERHADAP ECONOMIC LITERACY SISWA DI SMPN 3 PETERONGAN JOMBANG - Mutsaniah, Muizzatul (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
The purpose of this study was to determine the effects of modernity and the student learning outcomes of the economy to student economic literacy. This study uses a quantitative approach to associative design. Population in this study was students of grade IX of 3rd State Junior High School of Peterongan, Jombang for academic year of 2012/2013 with total of 224 students. Sample was 144 students, selected by using simple random sampling. Data analysed using multiple regression analysis. The results showed that there is a significant effect of modernity students to student economic literacy. There is no significant effect of economic learning outcomes to student economic literacy. There are significant effects of modernity and student learning outcomes of the economy to student economic literacy.